Journalistic code of ethics and journalists' liability for damages - Čeferin, Rok (Teorija in praksa, 2017)
The authors examine the position of the Supreme Court of the Republic of Slovenia regarding the relationship between violations of a journalistic ethics code and journalists' liability for damages. The analysis of its case law confirms that the court considers a journalist's (non-)compliance with the provisions of a journalistic code of ethics as one of the criteria for determining the acceptability of conduct as an element of liability for damages. However, the court has been inconsistent regarding its reference to the code. The authors argue that only clear, well-reasoned and uniform case law in this area will ensure greater legal certainty with respect to these legal questions.
Keywords: etični kodeksi; Journalism; Journalist code; Liability for damages; Novinarski kodeks; Novinarstvo; Odškodninska odgovornost; poklicna etika; Practice of law; Sodna praksa